Is It Decent Work? Role Ambiguity, Hustle Culture, Leisure Conflict - Ary Priambodo (Universitas Bunda Mulia, 2026)
This study examines the relationship between role ambiguity, hustle culture, and work-leisure conflict among employees in Jakarta, Indonesia. As the country’s primary economic hub, Jakarta is characterized by high work demands that may blur the boundaries between work and leisure. Understanding the organizational factors that contribute to this imbalance is important in supporting the achievement of decent work under Sustainable Development Goal (SDG) 8. This study employed a cross-sectional survey design using an online questionnaire distributed to employees working in Jakarta. A total of 193 valid responses were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that role ambiguity has a positive and significant effect on work-leisure conflict. Role ambiguity also positively influences hustle culture, while hustle culture significantly increases work-leisure conflict. Furthermore, hustle culture mediates the relationship between role ambiguity and work-leisure conflict. These findings suggest that unclear job expectations may encourage excessive work involvement and reinforce workaholic norms. Managerially, organizations should reduce role ambiguity by providing clear job descriptions, performance expectations, and communication to prevent the normalization of excessive work practices that may undermine employees’ opportunities for leisure and recovery.